Cytogenetic verification of Curcuma candida (Zingiberaceae) from Thailand and Myanmar - Nopporncharoenkul, Nattapon; Jenjittikul, Thaya; Chuenboonngarm, Ngarmnij; Anamthawat-Jónsson, Kesara; Umpunjun, Puangpaka (Thai Forest Bulletin (Botany), 2020)
Curcuma candida is a conservation-vulnerable species, rare and endemic to the Tenasserim Range (Thio Khao Tanaosri). This species was initially classified into the genus Kaempferia, based on morphology of specimen from Myanmar, and was given the name K. candida in 1830, but the first specimen from Thailand was only discovered in 2000. With the addition of molecular evidence, the species was transferred to Curcuma. The aim of the present study was therefore to find cytogenetic identity of C. candida, by investigating mitotic and meiotic divisions of five accessions obtained from the border districts of Thailand and Myanmar, in comparison with previous cytogenetic records of Curcuma and Kaempferia. The results show that C. candida is diploid with 2n = 42 and there is no variation among accessions. All accessions showed meiotic figure representing 21 bivalents during microsporogenesis, indicating the secondary base number x = 21. These chromosomal characteristics are closely similar to those found in diploid Curcuma species. The present paper also includes field observation and description of the plant phenology. The work has underlined an urgent need to protect this species in nature. During the sample collection trips we witnessed an excessive collection of edible flowers for local consumption.